Advances in bioanalytical techniques to measure steroid hormones in serum. (June 2016) - French, Deborah
Steroid hormones are measured clinically to determine if a patient has a pathological process occurring in the adrenal gland, or other hormone responsive organs. They are very similar in structure making them analytically challenging to measure. Additionally, these hormones have vast concentration differences in human serum adding to the measurement complexity. GC–MS was the gold standard methodology used to measure steroid hormones clinically, followed by radioimmunoassay, but that was replaced by immunoassay due to ease of use. LC–MS/MS has now become a popular alternative owing to simplified sample preparation than for GC–MS and increased specificity and sensitivity over immunoassay. This review will discuss these methodologies and some new developments that could simplify and improve steroid hormone analysis in serum.